Caveolin‐1 deficiency induces premature senescence with mitochondrial dysfunction. Issue 4 (17th May 2017) - Yu, Dong‐Min; Jung, Seung Hee; An, Hyoung‐Tae; Lee, Sungsoo; Hong, Jin; Park, Jun Sub; Lee, Hyun; Lee, Hwayeon; Bahn, Myeong‐Suk; Lee, Hyung Chul; Han, Na‐Kyung; Ko, Jesang; et al.
Summary: Paradoxical observations have been made regarding the role of caveolin‐1 (Cav‐1) during cellular senescence. For example, caveolin‐1 deficiency prevents reactive oxygen species‐induced cellular senescence despite mitochondrial dysfunction, which leads to senescence. To resolve this paradox, we re‐addressed the role of caveolin‐1 in cellular senescence in human diploid fibroblasts, A549, HCT116, and Cav‐1 −/− mouse embryonic fibroblasts. Cav‐1 deficiency (knockout or knockdown) induced cellular senescence via a p53‐p21‐dependent pathway, downregulating the expression level of the cardiolipin biosynthesis enzymes and then reducing the content of cardiolipin, a critical lipid for mitochondrial respiration. Our results showed that Cav‐1 deficiency decreased mitochondrial respiration, reduced the activity of oxidative phosphorylation complex I (CI), inactivated SIRT1, and decreased the NAD + /NADH ratio. From these results, we concluded that Cav‐1 deficiency induces premature senescence via mitochondrial dysfunction and silent information regulator 2 homologue 1 (SIRT1) inactivation.